Evaluation of Prophylactic and Therapeutic Effects of Tramadol and Tramadol Plus Magnesium Sulfate in an Acute Inflammatory Model of Pain and Edema in Rats - Srebro, Dragana; Vučković, Sonja; Milovanović, Aleksandar; Savić Vujović, Katarina; Prostran, Milica (Frontiers in Pharmacology, 2018)
Background: Inflammatory pain is the most commonly treated clinical pain, since it develops following trauma or surgery, and accompanies rheumatic or arthritic diseases. Tramadol is one of the most frequently used opioid analgesics in acute and chronic pain of different origin. Magnesium is a widely used dietary supplement that was recently shown to be a safe analgesic drug in different models of inflammatory pain. Aim: This study aimed to evaluate the effects of systemically or locally injected tramadol with/without systemically injected magnesium sulfate in prophylactic or therapeutic protocols of application in a rat model of somatic inflammatory hyperalgesia. Methods: Inflammation of the rat hind paw was induced by an intraplantar injection of carrageenan (0.1 mL, 0.5%). The antihyperalgesic effects of tramadol (intraperitoneally or intraplantarly injected), and tramadol-magnesium sulfate (subcutaneously injected) combinations were assessed by measuring the changes in paw withdrawal thresholds induced by carrageenan, with an electronic Von Frey anesthesiometer. The drugs were administered before or after inflammation induction. Results: Systemically administered tramadol (1.25-10 mg/kg) before or after induction of inflammation reduced mechanical hyperalgesia with a maximal antihyperalgesic effect of about 50-100%. Locally applied tramadol (0.125 mg/paw) reduced pain from 20 to 50% during 24 h. Magnesium sulfate (5 and 30 mg/kg) dose-independently reduced hyperalgesia when administered before or after induction of inflammation. In combination experiments, administration of a fixed dose of tramadol (1.25 mg/kg) with different doses of magnesium led to a dose-dependent enhancement and prolongation of the analgesic effect of tramadol both in prevention and treatment of inflammatory pain. Conclusions: According to results obtained in this animal model, systemic administration of low doses of tramadol and magnesium sulfate given in combination is a potent, effective and relatively safe therapeutic option for prevention and especially therapy of somatic inflammatory pain. The best result is achieved when tramadol is combined with magnesium sulfate at a dose that is equivalent to the average human recommended daily dose and when the drugs are administered when inflammation is maximally developed.